KEWENANGAN DAERAH DALAM PEMBENTUKAN PERDA PENANGGULANGAN PELACURAN - Maryati Maryati (Jurnal LEX SPECIALIS, 2012)
Abstract Prostitution is a social and humanitarian issues are serious because such actions are contrary to religious norms, customs, and morals as well as the negative impact on the lives of individuals, families and society as well as degrading human dignity. Therefore, it must be addressed. However, for the purposes of the law is still found even in the form of a legal vacuum. Along with regional autonomy based on the existing laws and the local government authority to establish local rules as the basis for prevention of prostitution in the area. Key Note : regional authority, prostitution